2009
DOI: 10.1002/glia.20859
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived cells in the central nervous system of a mouse model of amyotrophic lateral sclerosis are associated with blood vessels and express CX3CR1

Abstract: Amyotrophic lateral sclerosis (ALS) is associated with increased numbers of microglia within the CNS. However, it is unclear to what extent bone marrow (BM)-derived cells contribute to this microgliosis. We have studied the adoptive transfer of green fluorescent protein (GFP)-labeled whole BM cells and BM from mice that express GFP only in CX(3)CR1+ cells (CX(3)CR1(+/GFP)) into the CNS of a murine model of ALS having over-expression of mutant superoxide dismutase (mSOD), and wt littermates. We find that most G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Our current work does not formally determine whether degenerating Iba1-positive cells are microglia and/or infiltrating monocytes. The extent of monocyte infiltration remains controversial in the field of ALS [9,12,42,1,46], contrary to Alzheimer's disease in which monocyte infiltration has been repeatedly observed [29,30]. Our gene expression results demonstrate consistent loss of El Oussini and collaborators 15 expression of multiple genes typical of homeostatic microglia but while the monocyte marker Ly6c1 remained unaffected (Fig 6).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Our current work does not formally determine whether degenerating Iba1-positive cells are microglia and/or infiltrating monocytes. The extent of monocyte infiltration remains controversial in the field of ALS [9,12,42,1,46], contrary to Alzheimer's disease in which monocyte infiltration has been repeatedly observed [29,30]. Our gene expression results demonstrate consistent loss of El Oussini and collaborators 15 expression of multiple genes typical of homeostatic microglia but while the monocyte marker Ly6c1 remained unaffected (Fig 6).…”
Section: Discussionsupporting
confidence: 47%
“…An open question is whether the toxic effect of macrophages is mediated by resident microglia and/or by infiltrating blood monocytes. The extent of monocyte infiltration during ALS in mouse models remains controversial, with one study observing major monocytic infiltration [9], and others only very little if any [12,42,1,46]. Recently, genome-wide characterization of microglial and monocyte expression patterns led to the identification of a molecular signature of homeostatic microglia.…”
Section: Introductionmentioning
confidence: 99%
“…Brain sections were analyzed using a Leica epifluorescence microscope with a Leica digital camera (Leica Microsystems, Germany). GFP + cells in the cortex, hippocampus and hypothalamus of 3 brain sections per mouse were manually counted as previously described [14]. The area of tissue evaluated was outlined using microscope analysis software and the cell density determined using the area measurement tool on the Leica microscope software (Leica Application Suite; Leica Microsystems, Switzerland) to determine the mean number of GFP + cells/mm 3 tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in transgenic mice harboring mutant superoxide dismutase (mSOD), the murine model of amyotrophic lateral sclerosis (ALS), microglia are activated and infiltration of BM-derived cells into the CNS is observed [40,41]. In fact, it was suggested that reducing mSOD levels specifically in microglia might inhibit disease progression [42], implying detrimental microglial contribution in ALS.…”
Section: Macrophage/microglia Activation During Challengementioning
confidence: 97%